Diverging Paths? The Impact of the COVID-19 Pandemic on Subjective Well-Being of the Solo Self-Employed and Employees in Germany (2019–2023) - Eileen Peters; Merle Pohlmeyer; Karin Schulze Buschoff (Social Indicators Research, 2025)
Previous research indicates that the self-employed have higher subjective well-being (SWB) than employees. However, during the COVID-19 pandemic, many self-employed individuals experienced exceptionally high levels of economic stress due to limited government and social security support. This is especially true of the solo self-employed (i.e., self-employed without employees). Drawing on nationally representative panel data spanning the years 2019–2023—and thus the onset, peak, and fading out of the pandemic—we used fixed-effects regression models to analyze the SWB trajectories of the solo self-employed and employees in Germany in terms of life satisfaction and job satisfaction. Our results show that SWB was only moderately affected in 2020 but declined steeply in 2021. Although life satisfaction recovered moderately in 2022 and 2023, it remained substantially lower than pre-pandemic levels. The life satisfaction of the solo self-employed decreased more strongly than that of employees in 2020 and 2021. Job satisfaction also saw a steep decline in 2021, with solo self-employed individuals experiencing a greater drop than employees. However, the job satisfaction of the solo self-employed returned to pre-pandemic levels in 2022, whereas that of employees continued to decline in 2022 and 2023. These insights shed light on how the SWB of different employment groups was affected during this unprecedented crisis and provide valuable information for more effective interventions in future crises.
Keywords: 300; Subjective well-being; COVID-19; Solo self-employed; Employees; Germany